Describing compassion fatigue from the perspective of oncology nurses in Durban, South Africa - Dorien Wentzel; Anthony Collins; Petra Brysiewicz (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2019)
Background: Caring for cancer patients can take a toll on the emotional health of oncology nurses, which may lead to compassion fatigue, resulting in decreased quality of nursing care, absenteeism and decreased retention of staff. Aim: The aim of this study was to describe compassion fatigue from the perspective of oncology nurses. This study is part of a larger mixed-methods action research study to develop an in-facility intervention to manage compassion fatigue in oncology nurses. Setting: This study was conducted at Durban, KwaZulu-Natal, South Africa. Methods: The research setting comprised one state hospital (with oncology clinics and wards), a private hospital (with oncology wards) and a hospice in Durban, KwaZulu-Natal, South Africa. Semi-structured individual interviews (guided by Figley’s Compassion Fatigue Process, 2005) were conducted with eight participants. Data were analysed using manifest content analysis. Results: Five categories emerged from the data, namely, emotional connection, emotional fatigue, emotional loss, blurring boundaries and acceptance. Conclusion: The findings revealed that oncology nurses are affected emotionally in caring for their patients, thus making them prone to compassion fatigue. Oncology nurses need to acknowledge compassion fatigue and be able to self-reflect on how they are managing (both positively and negatively) with the stressors encountered in the oncology wards or units.